2022
DOI: 10.1186/s12967-022-03688-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics features for assessing tumor-infiltrating lymphocytes correlate with molecular traits of triple-negative breast cancer

Abstract: Background Tumor-infiltrating lymphocytes (TILs) have become a promising biomarker for assessing tumor immune microenvironment and predicting immunotherapy response. However, the assessment of TILs relies on invasive pathological slides. Methods We retrospectively extracted radiomics features from magnetic resonance imaging (MRI) to develop a radiomic cohort of triple-negative breast cancer (TNBC) (n = 139), among which 116 patients underwent trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 55 publications
(47 reference statements)
0
20
0
Order By: Relevance
“…Hectors et al found that texture features could reflect immune status in HCC patients, and were highly correlated with mRNA and protein expression of PDL1 and the markers of macrophages (CD68) and T cells (CD3) [ 23 ]. Su et al developed a radiomics model for tumor-infiltrating lymphocyte status based on GLCM and GLSZM texture features [ 40 ]. Ming et al also revealed that cell cycle pathway exhibited significant associations with SurfaceVolumeRatio (PRF9 and PRF10 in our study) [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hectors et al found that texture features could reflect immune status in HCC patients, and were highly correlated with mRNA and protein expression of PDL1 and the markers of macrophages (CD68) and T cells (CD3) [ 23 ]. Su et al developed a radiomics model for tumor-infiltrating lymphocyte status based on GLCM and GLSZM texture features [ 40 ]. Ming et al also revealed that cell cycle pathway exhibited significant associations with SurfaceVolumeRatio (PRF9 and PRF10 in our study) [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of individual immune cell types in TIME was inferred using the CIBERSORT interface [ 39 ], which estimated the relative fraction of immune cell types based on the deconvolution method. The gene sets of immune-related molecules were compared by GSVA, including cell surface immune-related molecules (costimulators, coinhibitors, and major histocompatibility complex) and cytokines (interleukins, chemokines, interferons, and colony-stimulating factors) [ 40 ]. Tumor immunogenicity was calculated by immunophenoscore (IPS) based on the gene expression in effector cells, immunosuppressive cells, MHC molecules, and immunomodulators [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Radiomics TILs score (Rad-TILs score), based on selected 3 radiomics features, was then juxtaposed with transcriptomics data concerning expression of several genes related to immunity. It has been shown that implemented radiomics model could be used to reflect lesions characterized with different immune patterns [ 66 ]. However, the role of MRI in estimating TILs density requires further analysis, particularly in the light of another recent report, which has shown that the combination of MRI radiomics and pathological TILs evaluation yielded the best results in assessing the efficacy of NAC compared to these methods alone.…”
Section: Breast Cancermentioning
confidence: 99%
“…Moreover, it has been estimated that around 50–70% of MRI findings requiring biopsy turn out to be non-cancer cases [ 5 ]. In recent years, radiomics and artificial intelligence have been increasingly applied in breast MRI [ 6 ], not only to classify breast lesions or predict response to treatment but also to differentiate benign from malignant lesions [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Indeed, radiological practice includes a qualitative and subjective evaluation of the visible lesion describing different characteristics of the tumor aspect (e.g., the presence of spiculations and the presence of necrosis and microcalcifications).…”
Section: Introductionmentioning
confidence: 99%